Amorphous phase stability and the interplay between electronic structure and topology. (1st June 2017) - Mahjoub, Reza; Laws, Kevin J.; Ferry, Michael
Abstract: It is well-known that the stability of Pd-Si amorphous alloys can be improved substantially by minor additions of alloying elements such as Cu and Ag. Such improvement in stability is explained herein, whereby microscopic models based on efficient atomic packing and electronic structure were applied to the results of first principles simulations of Pd82 Si18, Pd77.5 Si16.5 Cu8 and Pd75 Si15 Cu7 Ag3 metallic glasses. It was revealed that while the atomic packing model fails to unequivocally explain the stabilizing effect of the binary Pd-Si alloy due to minor additions of Cu and/or Ag, the contribution of electronic states with lower energies to the stability of the amorphous structure is increased markedly. Further, the observed enhancement in the compressive ductility as a result of the addition of Ag to the Pd77.5 Si16.5 Cu8 alloy can be correlated to the combined effects of an increased heterogeneity in the local topology, weakened covalency and, hence, reduced directionality of Pd-Pd bonds as well as enhanced metallicity in the Pd75 Si15 Cu7 Ag3 amorphous alloy. The analysis was further expanded to amorphous alloys where their characteristic binary prototypes are synthesised from late transition metals and non-metals as well as those comprising early transition metals and late transition metals. The findings shed light on the effects of minor alloying on the cooperative and competitive relationship between the topological and electronic structure of amorphous alloys. Graphical abstract: Image